Causal linkages between work and life satisfaction and their determinants in a structural VAR approach - Alex Coad; Martin Binder (Max Planck Institute of Economics, 2013)
Work and life satisfaction depend on a number of pecuniary and non-pecuniary factors at the workplace and determine these in turn. We analyze these causal linkages using a structural vector autoregression approach for a German sample of the working populace from 1984-2008.
Keywords: 330